Direct 3‐D printing of Ti‐6Al‐4V/HA composite porous scaffolds for customized mechanical properties and biological functions. (15th February 2020) - Yi, Tao; Zhou, Changchun; Ma, Liang; Wu, Lina; Xu, Xiujuan; Gu, Linxia; Fan, Yujiang; Xian, Guang; Fan, Hongyuan; Zhang, Xingdong
Abstract: Customized scaffold plays an important role in bone tissue regeneration. Precise control of the mechanical properties and biological functions of scaffolds still remains a challenge. In this study, metal and ceramic biomaterials are composited by direct 3‐D printing. Hydroxyapatite (HA) powders with diameter of about 25 μm and Ti‐6Al‐4V powders with diameter of 15–53 μm were mixed and modulated for preparing 3‐D printing inks formulation. Three different proportions of 8, 10, and 25 wt.% HA specimens were printed with same porosity of 72.1%. The green bodies of the printed porous scaffolds were sintered at 1, 150°C in the atmosphere of argon furnace and conventional muffle furnace. The porosities of the final 3‐D‐printed specimens were 64.3 ± 0.8% after linear shrinkage of 6.5 ± 0.8%. The maximum compressive strength of the 3‐D‐printed scaffolds can be flexibly customized in a wide range. The maximum compressive strength of these scaffolds in this study ranged from 3.07 to 60.4 MPa, depending on their different preparation process. The phase composition analysis and microstructure characterization indicated that the Ti‐6Al‐4V and HA were uniformly composited in the scaffolds. The cytocompatibility and osteogenic properties were evaluated in vitro with rabbit bone marrow stromal cells (rBMSCs). Differentiation and proliferation of rBMSCs indicated good biocompatibility of the 3‐D‐printed scaffolds. The proposed 3‐D printing of Ti‐6Al‐4V/HA composite porous scaffolds with tunable mechanical and biological properties in this study is a promising candidate for bone tissue engineering.